2003
DOI: 10.1161/01.res.0000065620.39919.20
|View full text |Cite
|
Sign up to set email alerts
|

A Breaker of Advanced Glycation End Products Attenuates Diabetes-Induced Myocardial Structural Changes

Abstract: Abstract-The formation of advanced glycation end products (AGEs) on extracellular matrix components leads to accelerated increases in collagen cross linking that contributes to myocardial stiffness in diabetes. This study determined the effect of the crosslink breaker, ALT-711 on diabetes-induced cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
298
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(326 citation statements)
references
References 60 publications
18
298
1
9
Order By: Relevance
“…As to the pathomechanisms involved, we found increased expression of ET-1, ET receptor, TGF-β and collagen IV in untreated STZ diabetic rats, confirming, at least in part, data of other laboratories [30,31,32]. A further finding of potential pathogenetic relevance was increased systolic blood pressure measured by tail plethysmography.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As to the pathomechanisms involved, we found increased expression of ET-1, ET receptor, TGF-β and collagen IV in untreated STZ diabetic rats, confirming, at least in part, data of other laboratories [30,31,32]. A further finding of potential pathogenetic relevance was increased systolic blood pressure measured by tail plethysmography.…”
Section: Discussionsupporting
confidence: 88%
“…The modification of extracellular matrix components by advanced glycation leads to increased collagen cross linking and increased myocardial stiffness in diabetes [31]. In addition our study showed increased expression for collagen IV in diabetic rats.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, cardiac BNP gene expression was reported to be increased and to improve by intervention with a breaker of advanced glycation endproducts in streptozotocin diabetic rats [28].…”
Section: Discussionmentioning
confidence: 99%
“…210 Advanced glycation is also related to alterations in myocardial calcium handling and hence contractility. 211 These findings could explain the electrophysiological alterations that serve as a central mechanism of the vulnerability to AF in diabetes. 212 Aggressive treatment of diabetes and adequate glycemic control may prevent or delay the occurrence of AF, despite little direct evidence of the effects of anti-diabetic drugs on AF.…”
Section: Diabetes Mellitusmentioning
confidence: 95%